2005
DOI: 10.1191/0267659105pf779oa
|View full text |Cite
|
Sign up to set email alerts
|

The intraoperative effect of pentoxifylline on the inflammatory process and leukocytes in cardiac surgery patients undergoing cardiopulmonary bypass

Abstract: CPB-related whole body inflammatory response could be partially inhibited by intraoperative PTX administration. This effect of PTX would be helpful in preventing the well-known complications of CPB-induced systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Measurements of inflammatory factors (i.e., white blood cell count and differentiation, C-reactive protein, TNF-α and -6) at 6 and 24 hoursIL postoperatively showed a significant reduction in the intervention group compared to the control group[23]. In our study we could not demonstrate significant effect of PTX on CRP in the first 24 hours after surgery.…”
Section: Discussioncontrasting
confidence: 73%
“…Measurements of inflammatory factors (i.e., white blood cell count and differentiation, C-reactive protein, TNF-α and -6) at 6 and 24 hoursIL postoperatively showed a significant reduction in the intervention group compared to the control group[23]. In our study we could not demonstrate significant effect of PTX on CRP in the first 24 hours after surgery.…”
Section: Discussioncontrasting
confidence: 73%
“…74 Owing to its anti-inflammatory properties, preoperative or intraoperative administration of pentoxifylline has been evaluated in a number of small-sized or moderate-sized controlled studies as an adjuvant to CPB. [75][76][77][78][79][80][81][82][83][84][85][86] Pentoxifylline has been administered orally in standard clinical doses for several days prior to surgery, or has been given intravenously at the time of surgery in various dose schedules (eg, 5 mg/kg as a bolus, followed by 1.5 mg/kg/h continuous infusion until 3 h after cessation of CPB). Many of these studies concluded that pentoxifylline administration decreased SIRS after CPB, as assessed by serum levels of proinflammatory cytokines such as TNF-α and IL-6.…”
Section: Slowing Of Progression Of Vascular Dementiamentioning
confidence: 99%
“…Another work in these patients had shown the incidence of multiple organ dysfunction syndrome (MODS) following CPB was 11%, with a mortality rate of 41% [6]. Various studies have investigated different methods to reduce this vigorous inflammatory response following cardiac surgery with CPB; include perioperative administration of corticosteroids [10], aprotinin [11], statins [12], pentoxifylline [13], milrinone [14], ketamine [15], and bovine intestinal alkaline phosphatase [16]. …”
Section: Discussionmentioning
confidence: 99%